Preparations of Nanostructured Silicide Bundles and Oxide Arrays - Tatsuoka, Hirokazu; Li, Wen; Meng, Erchao; Ishikwa, Daisuke; Nakane, Kaito; Oda, Shingo; Matsushita, Tomoji; Kurebayashi, Natsuki (UI Scholars Hub, 2014)
A variety of nanostructured silicide bundles and oxide nanowire arrays with abundant, non-toxic materials we are prepared. The CrSi2 nanowire and Mg2Si/MgO composite nanowire bundles were synthesized using a Si substrate and a SiOx nanofiber bundle, respectively. The hexagonal MoSi2 nanosheet bundles were also synthesized using a MoS2 layered material as a template. In addition, ZnO, CuO/Cu2O and a-Fe2O3 nanowire arrays were prepared on semiconductor or metallic substrates. The growth phenomena and the structural properties of the nanostructured materials awere investigated. In addition, the preparations of axial and radial nanowire structures weare examined.